Faktor Yang Mempengaruhi Return Saham Perusahaan Sektor Consumer Goods Dengan Ukuran Perusahaan Sebagai Variabel Moderasi Yang Terdaftar Di Bursa Efek Indonesia Tahun 2021-2023 - Warjana, Putu Erik; Padnyawati, Kadek Dewi; Ayu, Putu Cita (Hita Akuntansi dan Keuangan, 2025)
This research aims to test and analyze the factors that influence stock returns of consumer goods sector companies with company size as a moderating variable listed on BEI in 2021-2023. These factors include Return on Equity (ROE) and Debt to Equity Ratio (DER). The population used in this research are companies that have gone public or are listed on the Indonesian Stock Exchange in the consumer goods sector from 2021 to 2023. The research sample was taken using purposive sampling, where the sample is used if it meets the following criteria: (1) The company has published a report financial statements every quarter during, (2) The company does not experience losses during 2021 to 2023. (3) Consumer goods companies that are not delisted or re-listed during 2021 to 2023. (4) Shares of each company are actively traded every quarterly during. The analysis technique used is SEM (structural equation model). The research results show that ROE has a positive and significant effect on stock returns. DER has no effect on stock returns. Company size is not able to moderate the relationship between ROE and stock returns. Company size is not able to moderate the relationship between DER and stock returns.